Percutaneous Endoscopic Gastrostomy Tube Removal for Patients With Advanced Dementia: Case Series Study - Hattori, Yukari (Ann Geriatr Med Res, 2019)
BACKGROUND: Although the notion of percutaneous endoscopic gastrostomy (PEG) tube placement for patients with dementia has been changing, the number of cases of PEG placement remains high as Japan has become a super-aged society. However, there is insufficient research about the clinical course of dementia patients with PEG, especially regarding PEG extubation after regaining full oral intake. This case series aimed to reveal the demographic data of patients who successfully underwent PEG extubation and to identify clinical factors that might help predict eventual resumption. METHODS: This retrospective case series was identified in a private, community-based long-term care hospital in Sapporo, Japan. Inclusion criteria for the series were: 1) age, ≥75 years, 2) diagnosis of any type of dementia, and 3) resumption of full oral intake after removal of PEG tubes. RESULTS: Eight female patients were identified. Decreased oral intake was triggered by acute medical conditions, such as infectious enteritis. A trial of oral intake was initiated mostly by speech therapists. A majority of the patients ate pureed food. The patients aged ≥85 years with advanced dementia could be weaned from PEG tubes. CONCLUSION: The series indicates that even patients with limited life expectancy could recover swallowing function by receiving appropriate guidance and care. Constant evaluation for swallowing function even after PEG insertion may be important for PEG extubation.